University of life, rational and communicative action of a social movement leader - Eloy Alves Filho; Vítor Souza Lima Blotta; Osvaldo Freitas de Jesus (Universidade Federal do Norte do Tocantins, 2021)
This article has as objective the understanding of the social actions performed by Lourival Soares da Silva, who stood out for a life dedicated to activism in the movements of rural workers acting for several years as president of the Rio das Pedras Settlement Association, in Uberlândia. To understand and analyze their actions, a qualitative, observational approach was used and also through semi-structured interviews, in the methodological perspective of oral history. The theoretical framework consisted of a combination of Max Weber's comprehensive sociology, which is based on the understanding of human conduct endowed with meaning, more specifically the rational action in relation to values, with Jürgen Habermas' theory of communicative action, centered on oriented actions by the intersubjective agreements that are revealed in language and communication. It is concluded that the meanings linked to the social actions carried out by the social movement leader are summarized in categories based on the values ​​of equality, justice, right to work, dialogue, democracy and collective social action. These ethical and emancipatory standards are not limited to their finalistic aspect, or their results, but above all in the value of a daily course that is very present in the imagination of social movements.